1995
DOI: 10.1016/0014-5793(95)01032-a
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and functional dissection of the galactin‐1 gene promoter

Abstract: The galectin-1 gene encodes a ~-galactoside-binding protein whose overexpression is associated with neoplastic transformation and loss of differentiation. Transient transfection assays of a series of deletions constructs (pGAT) showed that the galectin-I promoter is highly active in cells both expressing and non-expressing the endogenous gene, and that the basal activity is determined by sequences encompassing the transcription start site (-50/+ 50). Both an upstream (-50/-26) and a downstream position-depende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 29 publications
0
27
0
Order By: Relevance
“…Seventeen CpG sites, natural substrates of mammalian methyltransferase, are located in this 5Ј region. Interestingly, the majority of these dinucleotides are clustered in a region of about 200 bp (positions Ϫ122 to ϩ81), encompassing the transcription start site, that is sufficient for basal promoter activity (45). A similar distribution of CpG doublets is present in the corresponding region of the mouse (11) and human (23) genes (Fig.…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…Seventeen CpG sites, natural substrates of mammalian methyltransferase, are located in this 5Ј region. Interestingly, the majority of these dinucleotides are clustered in a region of about 200 bp (positions Ϫ122 to ϩ81), encompassing the transcription start site, that is sufficient for basal promoter activity (45). A similar distribution of CpG doublets is present in the corresponding region of the mouse (11) and human (23) genes (Fig.…”
Section: Resultsmentioning
confidence: 76%
“…On the other hand, galectin-1 promoter constructs are transactivated by factors present in both expressing and nonexpressing cells (45). To explain this, we postulated that the gene is repressed in nonproducing cells, through a cis-acting mechanism which is nonfunctional on transiently transfected promoters, and is derepressed in the hybrids in a dominant fashion.…”
mentioning
confidence: 99%
“…Next we questioned whether MBDin could reactivate transcription from methylated promoters. For this purpose we used a plasmid construct containing 1,700 bp of the mouse galectin-1 promoter upstream of a CAT reporter gene (pGAT1700) (36). It was previously demonstrated that galectin-1 promoter constructs are repressed by in vitro DNA methylation (4).…”
Section: Resultsmentioning
confidence: 99%
“…Among the parsimony reconstructions (i.e., ACCTRAN and DELTRAN) and maximum likelihood (ML) reconstructions of ancestral states on the species tree, several functionally important replacements occurred in which derived cysteines would have resulted LGALS1 directs the transcription of two distinct-length mRNAs encoding for the same protein in humans and mice, and the transcription initiation for both transcripts is mediated by the Inr, TATA box, and SP1 binding site, the latter of which is crucial for the basal LGALS1 expression (35)(36)(37)(38). From the conserved cis elements (AP-2, yellow boxes; AP-4, black boxes, CAAT box-binding protein, white boxes; CAC-binding protein, gray boxes; C/EBP-␣, pink boxes; c-ETS-2, brown boxes; ERE, red boxes; HSF-1, orange boxes; NF-1, light blue boxes, NF-Y, dark blue boxes; and SP1, green boxes), 10 have been gained on the stem of placental mammals.…”
Section: C) (D)mentioning
confidence: 99%
“…Indeed, the stem of placental mammals underwent a gain of 10 cis elements, including a highly conserved half ERE, an overlapping NF-Y, and a nearby AP-2 motif, which were identified in humans and mice but functionally not yet characterized (35)(36)(37). Estrogens act through estrogen receptors that are involved in the stimulation of uterine growth, progesterone receptor expression, and immunoregulation (39).…”
Section: Ere May Participate In Regulation Of Uterine/placentalmentioning
confidence: 99%